Evaluation of Structure, Content and Quality of Morning Report Sessions in Ahvaz jundishapur University of Medical Sciences - Khajeali, Nasrin; Ahmadi, Fatemeh; Heidari, Sara; Aslami, Maryam; Kalantarion, Masoumeh; Najaf Kochak, Marzieh (International Journal of Education and Cognitive Sciences, 2022)
Morning report is an important and influential method in the clinical training of the medical field. This program has some characteristics and standards that, when properly applied, will play an effective role in students’ clinical learning. The main aim of this study is to the evaluation of structure, content, and quality of morning report sessions in internal medicine wards affiliated with Jundishapur University of Medical Sciences, and also to assess students’ viewpoints on the structure, content, and quality of morning report sessions. In this cross-sectional study, the structural characteristics of morning report sessions and the students’ rate of benefit from their content were investigated in the year 2019-2020. A sample of 224 internship and clerkship medical students were asked to fill in a standard questionnaire. The validity and reliability were confirmed by experts and the calculation of Cronbach’s alpha respectively. The mean duration of morning reports was 57/30±12/5 minutes. The average number of meetings was 5 times a week, the average duration of sessions was 16 minutes, the patient presenter in most cases was a senior resident, the cases presented were complicated ones, the leader of sessions was one of the specialist professors. The main audience at the sessions was not defined. Usually, the experts of other fields such as pharmacists, nutritionists, pathologists, or radiologists were absent. The total benefit rate according to the students was 42 people (18.5%) high, 115 people (51%) moderate and 67 people (30.5%) low. There was a significant correlation between their benefit rate and most of the structural parameters of morning report sessions (P